2022
DOI: 10.3389/fsurg.2022.863078
|View full text |Cite
|
Sign up to set email alerts
|

The Transumbilical Laparoendoscopic Single-Site Extraperitoneal Approach for Pelvic and Para-Aortic Lymphadenectomy: A Technique Note and Feasibility Study

Abstract: BackgroundNowadays, lymphadenectomy could be performed by the transperitoneal or extraperitoneal approach. Nevertheless, each approach has its own advantages and disadvantages. Under these circumstances, we developed a transumbilical laparoendoscopic single-site (TU-LESS) extraperitoneal approach for lymphadenectomy. In this research, the primary goal is to demonstrate the feasibility of the novel approach in systematic lymphadenectomy and present the surgical process step-by-step.MethodsBetween May 2020 and J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The flexibility of the device at times also made it difficult to place it to access the abdominal cavity, influencing the total surgery time since, when the flexible portion broke, it was necessary to assemble a new device and restart its placement through the minilaparotomy. In this case, it is suggested that the flexible portion of the new device be produced with a more consistent, resistant, versatile, durable, and low-cost material, such as synthetic or semi-synthetic plastic, or even with a material produced by latex [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…The flexibility of the device at times also made it difficult to place it to access the abdominal cavity, influencing the total surgery time since, when the flexible portion broke, it was necessary to assemble a new device and restart its placement through the minilaparotomy. In this case, it is suggested that the flexible portion of the new device be produced with a more consistent, resistant, versatile, durable, and low-cost material, such as synthetic or semi-synthetic plastic, or even with a material produced by latex [21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in the left-sided abdominal approach of EPA ( Figure 2(a) ), lymph node dissection between the aorta and inferior vena cava or on the right side of the inferior vena cava becomes somewhat difficult due to the field of view. Peng et al reported EPA with an umbilical single port, which allows EPA to have a view from the caudal side, similar to TPA [ 9 ]. For TPA, Mizumoto et al reported an approach from the left side of the descending colon called left dome formation, in which the left ovarian vein and left ureter can be followed all the way from the caudal side, ultimately providing a view exactly like that of the left-sided approach of EPA [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus we designed an innovative extraperitoneal approach through the same umbilical incision which achieves satisfactory visualization and lymph node retrieval of both pelvic and para-aortic areas 3 4. Also, we found that the approach was particularly suitable for fertility sparing because it can maintain an intact peritoneum and reduce intraperitoneal adhesion, which might contribute to a future pregnancy.…”
mentioning
confidence: 99%